Menggugah Partisipasi Kaum Perempuan dalam Pemberantasan Tindak Pidana Korupsi - Nanik Triandayani (Millah: Journal of Religious Studies, 2006)
This article describes the relation woman and corruption, and woman’s participation to fight against the corruption. Woman can be the corruptor direct or indirectly. Woman can be a supported factor for their husbands to corrupt. Even though, like man, woman has some a capacities to fight against corruption that increases in every bureaucracy in this country. This participation is not only interpreted and focus informal area, but also in informal area. As housewife, woman can manifest this struggle by educating good moral to every member of family. A sa wife, woman can influences husbands behavior.